The Effects of Virtual Classroom & Virtual Labs and Internet on Learning as A Triangle Interaction - Myasah Hamoud Ali Yahiya alhumaidy; Gamal Ahmed. Ahmed. Abdullah Alawi (Taez University, 2024)
This study aims to use virtual classroom (V Class), Virtual Labs (VLabs), and Internet Support (IntSup) technologies-based simulations that is interesting, easy to use by participants and streamline the time of technical teachers in bringing the technical materials as well as feasible to be used in learning anywhere and anytime. These technologies used both the practical of math course and theory in the government schools in Taiz city, Yemen as the most significant tools of information age and could be used in each stage of education system. This paper has been designed to study the adoption of the participants of the general class towards the VClass and VLabs simulations' usage with Internet support in three dimensions of their abilities, practical skills and knowledge. The interaction between these dimensions is the key purpose of this study to integrate technology in existing educational approach and introduce new technologies as an important tool to support new ways of practical teaching and learning. A model, which explains the effect of V Class, V Labs, IntSup and Teach Online on learning, is established and tested. Using AMOS 21 (Analysis of Moment Structures) program, it explains (100%) of V Class tools, (46%) of V Labs tools, (91 %) of Intsup and (83%) of Teach Online, with good model fit. All hypotheses are accepted which is indicated by the findings of this study.